Bariatric Surgery as a Molecular Modulator: The Role of FSHR Polymorphisms in Enhancing eNOS Expression and Reproductive Hormone Dynamics in Women with Severe Obesity - Charalampos Voros; Despoina Mavrogianni; Kyriakos Bananis; Alexios Karakasis; Anthi-Maria Papahliou; Vasileios Topalis; Antonia Varthaliti; Raphail Mantzioros; Panagiota Kondili; Menelaos Darlas; Regina Sotiropoulou; Diamantis Athanasiou; et al. (Biomedicines)
Background/Objectives: Severe obesity (BMI > 40 kg/m2) has a severe influence on vascular health and reproduction. This study looks at how bariatric surgery affects endothelial nitric oxide synthase (eNOS) expression and reproductive hormone regulation across different follicle-stimulating hormone receptor (FSHR) polymorphism groups in women with extreme obesity. Methods: Twenty-nine women with extreme obesity had bariatric surgery. Pre- and post-surgery levels of eNOS and reproductive hormones such as follicle-stimulating hormone (FSH), sex hormone-binding globulin (SHBG), anti-Müllerian hormone (AMH), and antral follicle count (AFC) were assessed. Patients were divided into three FSHR polymorphism groups (Ser/Ser, Asn/Asn, and Ser/Asn), and results were compared between them. Statistical techniques were used to determine changes and relationships. Results: Bariatric surgery led to substantial increases in eNOS expression across all FSHR polymorphism groups (p < 0.0001), with the Ser/Ser group exhibiting the most variability. Prior to surgery, the Ser/Ser group had substantially higher FSH levels (7.41 ± 0.60 mIU/mL) than the Asn/Asn group (5.20 ± 0.63 mIU/mL, p < 0.001). Following surgery, FSH levels rose in the Ser/Ser group (9.45 ± 0.87 mIU/mL), with significant differences between the Ser/Ser and Ser/Asn groups (mean difference = 0.97, p = 0.019). SHBG levels had a negative connection with eNOS expression after surgery (r = −0.365, p = 0.049). AMH and AFC remained constant throughout polymorphism groups. BMI decreased uniformly, with an average of 15.2 ± 1.8 kg six months after surgery. Conclusions: Bariatric surgery improves vascular health and regulates reproductive hormones, especially in individuals with the Ser/Ser genotype. These findings indicate the possibility of combining genetic testing and bariatric therapies to improve infertility treatment in obese women.